Commonist Tendencies: Mutual Aid beyond Communism - Shantz, Jeff (punctum books, 2013)
As capitalist societies in the twenty-first century move from crisis to crisis, oppositional movements in the global North have been somewhat stymied (despite ephemeral manifestations like Occupy), confronted with the pressing need to develop organizational infrastructures that might prepare the ground for a real, and durable, alternative. More and more, the need to develop shared infrastructural resources - what Shantz terms "infrastructures of resistance" - becomes apparent. Ecological disaster (through crises of capital), economic crisis, political austerity, and mass produced fear and phobia all require organizational preparation - the common building of real world alternatives. There is, as necessary as ever, a need to think through what we, as non-elites, exploited, and oppressed, want and how we might get it. There is an urgency to pursue constructive approaches to meet common needs. For many, the constructive vision and practice for meeting social needs (individual and collective) is expressed as commonism - an aspiration of mutual aid, sharing, and common good or common wealth collectively determined and arrived at. The term commonsim is a useful way to discuss the goals and aspirations of oppositional movements, the movement of movements, because it returns to social struggle the emphasis on commonality - a common wealth - that has been lost in the histories of previous movements that subsumed the commons within mechanisms of state control, regulation, and accounting - namely communism.